Oleaginous yeasts for sustainable lipid production - from biodiesel to surf boards, a wide range of "green" applications - Bruno Vasconcelos (2019)
A growing world population and a growing number of applications for vegetable oils are generating an increasing demand for these oils, causing serious environmental problems. A sustainable lipid production is then fundamental to address these problems. Oleaginous yeasts are a promising solution for sustainable lipid production, but, with the current knowledge and technology, they are still not a serious alternative in the market. In this review, the potential of these yeasts is highlighted and a discussion is made mainly focused on the economics of the oleaginous yeast oil production and identification of the key points to be improved to achieve lower production costs and higher income. Three main stages of the production process, where costs are higher, were identified. To render economically feasible the production of oils using oleaginous yeasts, a reduction in production costs must occur in all stages, lipid yields and productivities must be improved, and production must be targeted to high-value product applications.